Acute Effects of Drop-Jump Protocols on Explosive Performances of Elite Handball Players. Issue 11 (November 2016) - Dello Iacono, Antonio; Martone, Domenico; Padulo, Johnny
Abstract : Abstract: Dello Iacono, A, Martone, D, and Padulo, J. Acute effects of drop-jump protocols on explosive performances of elite handball players. J Strength Cond Res 30(11): 3122–3133, 2016—This study aimed to assess the acute effects of vertical and horizontal drop jump–based postactivation potentiation (PAP) protocols on neuromuscular abilities in tasks such as jumping, sprinting, and change of direction (COD). Eighteen handball players were assessed before and after PAP regimens, consisting of either vertical single-leg drop-jumps (VDJ) or horizontal single-leg drop-jumps (HDJ) single-leg drop-jumps, on countermovement jump (CMJ), linear sprint, shuttle sprint, and agility performance. The HDJ led to greater improvement of the COD performance in comparison with the VDJ (−6.8 vs. −1.3%; p ⩽ 0.05), whereas the VDJ caused greater improvement in the CMJ task compared with the HDJs (+6.5 vs. +1%; p ⩽ 0.05). Moreover, the VDJ regimens compared with HDJ induced greater changes in most of the kinetic variables associated with vertical jumping performance, such as peak ground reaction forces (+9.6 vs. +1.3%), vertical displacement (−13.4 vs. −5.3%), leg-spring stiffness (+18.6 vs. +3.6%), contact time (−9.2 vs. −1.3%), and reactive strength index (+7.3 vs. +2.4%) (all comparisons with p ⩽ 0.05). Conversely, the HDJ regimens were able to improve the COD performance only by reducing the contact time on COD more than the VDJ (−13.3 vs. −2.4% with p ⩽ 0.05). The results showed that both PAPs were able to improve the performances that specifically featured similar force-orientation production. This investigation showed the crucial role that different and specific PAP regimens play in optimizing related functional performances. Specifically oriented vertical and horizontal single-leg drop-jump protocols represent viable means for achieving enhanced explosive-based tasks such as jumping and COD.